Descriptive Study Of Handling Dyslexic Students At Public Elementary School 2, Banyuwangi - Lilin Andi Maria; Imas Diana Aprilia (International Inclusion Development and Cooperation, 2023)
The aim of this research is to describe how teachers recognize dyslexic children, how they collaborate to develop treatment programs, and their strategies for handling dyslexic children. The research method used is qualitative descriptive, with procedures starting from determining the focus, collecting data, analyzing data using Miles and Huberman's interactive model technique, determining and selecting research attributes, evaluating data validity using triangulation of sources and techniques, and reporting the research results. The findings of the research are as follows: (1) Teachers have been able to identify dyslexic children through the teaching and learning process. (2) Collaboration between schools and parents has been established since the first day of school. (3) Dyslexic children are not given special learning media and methods; instead, they are given additional time to complete their school tasks. Treatment for dyslexic children is not differentiated from regular children generally.